Pengaruh Service Quality, Promotion, dan Convenience Penggunaan Aplikasi KAI Access Terhadap Customer loyalty Melalui Customer Satisfaction PT Kereta Api Indonesia (Politeknik Perkeretaapian Indonesia Madiun, 2023)
Occurrence of transaction that utilize online media to improve communication between buyers and sellers is one of the indicators of technological progress in business field. With the advancement of internet technology, consumers now have instant access to all their needs, making online transactions. a necessity for many people. Transportation today can be seen as effective in limiting distance and time constraints. By allowing people to travel in greater numbers and regularly or continuously and more frequently, the advancement and development of transportation in the modern era can drive an increase in human needs. Kereta api Indonesia or known as KAI (Kereta Api Indonesia) is one type of land transportation in Indonesia.This train ticket booking application known as KAI Access was developed and released by PT KAI (Kereta Api Indonesia). To accommodate the requirements of long-distance, medium-distance, and local/commuter train passengers, PT KAI launched an official application named KAI Access. The motivation behind this examination is to ascertain the impact service quality, promotion, and convenience of using the KAI Access application of customer loyalty through PT Kereta Api Indonesia's customer satisfaction. This study employs a quantitative approach. This study discovered that PT Kereta Api Indonesia's customers are significantly more loyal to the company due to the service quality, promotion, and convenience of the KAI Access application.